2011
DOI: 10.1063/1.3627151
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio virial equation of state for argon using a new nonadditive three-body potential

Abstract: An ab initio nonadditive three-body potential for argon has been developed using quantum-chemical calculations at the CCSD(T) and CCSDT levels of theory. Applying this potential together with a recent ab initio pair potential from the literature, the third and fourth to seventh pressure virial coefficients of argon were computed by standard numerical integration and the Mayer-sampling Monte Carlo method, respectively, for a wide temperature range. All calculated virial coefficients were fitted separately as po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
124
1
11

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(152 citation statements)
references
References 70 publications
(93 reference statements)
16
124
1
11
Order By: Relevance
“…Here we show that a seventh-order ab initio virial EOS for argon [20][21][22] gives rise to (high-temperature) JT inversion data in excellent agreement with the reference data set 5 up to the maximum inversion pressure. We also argue that the obtained JT inversion curves provide some insight into the range of applicability and high-density behavior of the truncated virial EOS.…”
Section: -20mentioning
confidence: 48%
See 1 more Smart Citation
“…Here we show that a seventh-order ab initio virial EOS for argon [20][21][22] gives rise to (high-temperature) JT inversion data in excellent agreement with the reference data set 5 up to the maximum inversion pressure. We also argue that the obtained JT inversion curves provide some insight into the range of applicability and high-density behavior of the truncated virial EOS.…”
Section: -20mentioning
confidence: 48%
“…Jäger et al have reported smooth temperaturedependencies of B 2 to B 7 in terms of fits (of Laurent polynomials in √ T ) to discrete B n data computed from ab initio two-body 21,22 and non-additive three-body potentials. 22 We use these fits to compute the JT inversion curve by solving…”
Section: -20mentioning
confidence: 99%
“…The hard-sphere fluid with a sphere diameter of 0.45 nm was used as reference system. Results for all temperatures were obtained simultaneously by performing multi-temperature simulations [22,37] with a sampling temperature of 150 K and 2 × 10 10 trial moves. For each trial move, one of the molecules was displaced and rotated.…”
Section: Cross Second Virial Coefficientsmentioning
confidence: 99%
“…Results for all temperatures were obtained simultaneously by performing multitemperature simulations 6,23,44 with a sampling temperature of 70 K and 2 × 10 10 trial moves. For each MC trial move, one of the molecules was displaced and rotated.…”
Section: Cross Second Virial Coefficientmentioning
confidence: 99%